MUSEALE RESTE - Samuel, Nina (2022)
Remnants challenge the institution of the museum. They are tipping figures that open up attributions and thus collaborate in transgressing the taxonomic, disciplinary, architectural and institutional boundaries of the museum. They can be found everywhere - in the exhibition space as well as in the depot, in the laboratory as well as in the administration. In each of these contexts, different forms of professional self-understanding, knowledge and practical interaction are available to determine the status of remains. The volume contributes to clarifying concepts such as rest, waste, traces, edges in the context of the museum and to re-evaluating them for debates in conservation, curation, art history and museum anthropology.